The Utilization of Technology in Corporate Social Responsibility Activities: A Case Study of Sido Muncul's Shared Value Program in Sambirata Village during the COVID-19 Pandemic - Ayu, Kilau Riksaning; Fuaddah, Ashlikhatul; Sutikna, Nana (Universitas Ahmad Dahlan, 2023)
Sido Muncul Company produces modern herbal medicines and has adopted the concept of creating shared value (CSV) to synergize community empowerment with their core business. They implemented a CSV program called Desa Rempah, which focuses on the potential of Sambirata Village's cardamom commodity. This study examines the utilization of technology in their CSV activities during the COVID-19 pandemic. This research utilized qualitative case study methods to gather primary and secondary data from various stakeholders, including companies, public relations officers, community development teams, and local leaders, to gain insights into implementing Corporate Social Responsibility (CSR) activities by PT Sido Muncul in Sambirata Village. The case study approach allowed for a subjective perspective on social reality and used theoretical propositions to generalize findings. The CSV program, Desa Rempah, addresses the company's need for raw materials and the farmer group's issues in processing cardamom. The COVID-19 pandemic posed challenges to CSV implementation. Still, the company adapted through digital transformations and prioritized the local community's efficiency and effectiveness in developing CSV activities with BumDes (Village Owned Enterprises) Sambirata. Sido Muncul's strategy for CSV activities involves social mapping research and collaboration with stakeholders, including government and Bumdes Sambirata, to create shared value through innovations and efficiency, effectiveness, and responsiveness. During the COVID-19 pandemic, the company collaborated with millennial farmers to overcome obstacles and increase farmers' independence, leading to higher-value dried cardamom and increased income for the farmer group.